Ciarra Leanne dela Cruz Journal Entry - dela Cruz, Ciarra Leanne::::::::: (2020)
Journal entry reflecting on experience with COVID-19 including a trip to the San Jose Municipal Rose Garden and social distancing visits with family. Includes 2 photos: San Jose Municipal Rose Garden and visiting sister to her cottage in Los Gatos.